V. Nazari, A. M. Cotton, J. G. Coutsis, N. Shapoval, V. Todisco & G. C. Bozano Guide to the Butterflies of the Palearctic Region part 4: Subfamily Papilioninae, Tribe Papilionini, Genus Papilio (partim) - Antonio Vives Moreno (SHILAP, 2024)
Revisión de Publicaciones